Analysis The Competitiveness of Indonesian Tobacco Exports to International Markets 2003-2022 - Nur Salsabila, Nadhifah; Tarik Ibrahim, Jabal; Mumpuni Ningsih, Gumoyo (International Journal of Scientific Research and Management (IJSRM), 2024)
Indonesia as an open economy country establishes trade relations with other countries in the world to sell excess and buy shortages of products needed by a country. International trade has two important activities, there are exports and imports. Both of these are the main activities that play a major role in a countrys economy. One way that a country can increase and improve its economic conditions is by increasing competitiveness through comparative and competitive advantage. One of the commodities from Indonesia that is demand in international market is tobacco. Tobacco is product from the leaves of Nicotiana genus that can be used as pesticides, medicines, and cigarettes. Therefore, this research aims to determine competitiveness of Indonesian tobacco exports comparatively and competitively through RCA and TSI analysis. This study also aims to find out whether Indonesian tobacco can win the market or not through AR analysis. The results obtained are the average value of RCA 2.12 indicates that Indonesian tobacco has a comparative advantage. The average value of TSI 0.21 indicates that Indonesian tobacco has a strong competitive advantage, tends to be an exporter country and Indonesia in export expansion period. The average value of AR 1.57 indicates that Indonesia is able to capture the tobacco market and Indonesias position is getting stronger in the export and domestic market. It can be concluded that Indonesian tobacco has comparative and competitive advantage and Indonesian tobacco is able to capture the tobacco market to international market.